Anticandidal Effects of Ethanolic Extract of Lada Katokkon (Capsicum annuum chinense) Against Emerging Fungal Pathogens - Allen Mangoting; Eka Astuty; Amanda Gracia Manuputty (Biology, Medicine, & Natural Product Chemistry, 2025)
Candidiasis is an opportunistic mycotic infection with a high prevalence, caused by Candida species, especially Candida albicans, Candida tropicalis, and Candida parapsilosis. The increasing resistance of Candida spp. to conventional antifungals such as fluconazole poses a challenge in the management of candidiasis, thus the need for natural-based alternatives, such as Lada Katokkon. This condition encourages the need to explore alternative therapeutic agents based on natural ingredients. Lada Katokkon (Capsicum annuum chinense Jacq), a local chili variety cultivated in the Toraja region, is known to contain secondary metabolite compounds such as capsaicin, flavonoids, saponins, and alkaloids that have potential as antifungals. This study aims to evaluate the antifungal activity of ethanol extract of Lada Katokkon against the growth of C. albicans, C. tropicalis, and C. parapsilosis in vitro using disc diffusion method. The extract was tested at five concentrations: 1%, 3%, 5%, 7%, and 9%. There was a positive relationship between extract concentration and inhibition zone diameter. The highest activity was recorded at 9% concentration, particularly against C. parapsilosis (16.89 ± 4.74 mm), followed by C. albicans (9.03 ± 5.96 mm) and C. tropicalis (8.07 ± 0.81 mm). In contrast, 1% concentration produced the lowest zone of inhibition in all species tested. These results suggest that ethanol extract of Lada Katokkon has potential as an alternative natural antifungal agent in candidiasis therapy.